Soil respiration response to reductions in maize plant density and increased row spacing (Southeast pampas, Argentina) - Lewczuk, Nuria (2024)
Previous studies have recognized the influence of crop cover and agricultural management on variables (soil temperature, soil moisture, and root biomass) that influence soil respiration. However, despite the influence of plant density and row spacing on these variables in the maize crop (Zea mays L.), their impact on soil respiration has received little attention. Thus, the aims of this study were (i) to investigate whether reducing plant density and row spacing influences soil respiration, and (ii) to identify the controlling variables (soil temperature and soil moisture) underlying this response. We conducted field experiments in Balcarce, Argentina, over two seasons. Treatments included (i) maize crops at high plant density (≈8 plants m−2) and narrow rows (0.52 cm, HDN), and (ii) maize crops at low plant density (≈6.5 plants m−2) and wide row spacing (0.70 cm; LDW). Leaf area index (LAI), soil CO2 fluxes, soil superficial temperature, and moisture (characterized by the water-filled pore space, WFPS) were assessed throughout the growing season. Grain yield and cumulative soil CO2 emissions were determined at the final harvest. Major findings relevant to understanding the influence of reducing plant density and wider row spacing on instant CO2 fluxes include: (i) LAI reductions were related to higher superficial soil moisture, which was consistent at LAI ≥ 3; suggesting higher decreases in water uptake than increases in soil evaporation, and in turn (ii) increments in soil moisture were associated with higher CO2 fluxes. While lower plant density and wider row spacing had notable short-term effects on WFPS and soil respiration fluxes, they did not significantly affect cumulative soil respiration throughout the growing season. However, the combination of this practice with low-yield potential genotypes that exhibit low stability to changes in resource availability can increase CO2 emissions per unit of grain yield. These findings contribute to a better understanding of the impacts of management practices on soil respiration and, consequently, on carbon cycling within agricultural ecosystems.